7‐T MRI of the spinal cord can detect lateral corticospinal tract abnormality in amyotrophic lateral sclerosis. Issue 5 (29th March 2013) - Cohen‐Adad, Julien; Zhao, Wei; Keil, Boris; Ratai, Eva‐Maria; Triantafyllou, Christina; Lawson, Robert; Dheel, Christina; Wald, Lawrence L.; Rosen, Bruce R.; Cudkowicz, Merit; Atassi, Nazem
<x xml:space="preserve">Abstract</x> Introduction: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder affecting lower and upper motor neurons. Degeneration of the lateral corticospinal tract (CST) is a key finding in ALS cervical spinal cord autopsies. We hypothesized that in vivo ultra‐high‐field MRI of the cervical spinal cord can detect abnormality in the CST. Methods: A patient with ALS (disease duration 23 months) and a healthy control were scanned at 7‐T MRI using a 19‐channel coil. Multi‐echo <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1xr38267" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />T2*‐weighted imaging was performed in the spinal cord, covering C2–C6. Cross‐sectional resolution was 0.37 × 0.37 mm2. Results: We detected clear signal hyperintensity in both segments of the lateral CST in the ALS patient, which was significant when compared with the normal control subject (P < 10−7). Conclusion: We believe there are potential benefits of 7‐T MRI for increased sensitivity and spatial accuracy in characterizing pathology in the spinal cord. Muscle Nerve 47: 760–762, 2013